Growth of tourism and microeconomic variables / Adila Hashim (Faculty of Business and Management, 2007)
A study on the microeconomic variables for the past 20 years from 1987 - 2006 compasses then growth of tourism industry. The study is to show how well Malaysia's performance in tourism industry. The effects of microeconomics changes that affect growth of tourism industry will be analyzed using regression analysis. Microeconomic variables selected for the studies that affect growth of tourism industry are foreign direct investment, employment anf inflation. The secondary data used in this research includes journals, Internet, reference books, Tourism Malaysia Annual Report and Tourism Malaysia Quarterly Bulletin. Finally, the result from all relevant analysis showed there is significant impact between foreign direct investment, employment and infaltion in explaining growth of tourism industry in Malaysia. Hopefully, this study can give some guidelines and information on the growth of tourism industry in Malaysia.